Fabriquer en Jordanie - Taher Labadi; Katharina Grüneisl (Revue des Mondes Musulmans et de la Méditerranée)
The creation of Qualified Industrial Zones (QIZs) in Jordan at the end of the 1990s provided a new connection to the global economy. The tariff exemptions granted to garments exported to the American market favoured the emergence of a clothing industry ex-nihilo, positioning Jordan as an attractive production location in the global value chain (GVC). As both a political and economic construct, the QIZ sector has remained largely exogenous to the Jordanian economy. It depends on foreign capital, migrant labour and the import of input materials for production. Nevertheless, this paper shows that the garment industry today occupies a central role in economic policies in Jordan. First, to achieve a strategic reconfiguration of transnational logistics routes in a region fragmented by conflict. Second, to enhance local linkages and benefits from the export-oriented garment industry through so-called “jordanisation” policies. As this paper demonstrates, such policies have in fact reinforced the extraterritorial character of the clothing sector, perpetuating its exemption from national labour regulation and expanding the incentives granted to foreign investors. At the same time, the resulting strategic partnerships with multinational clothing producers have enhanced the scope of state action. Taken together, this paper advances an analysis of extra-territorialities of the global economy as central devices for performing the Jordanian nation state.